Till Death Do Us Part: The Ailment Affecting the Widow’s Life Interest in Kenyan Intestate Succession - Badbess, Khalil (Strathmore Law Review, 2019)
Succession law in Kenya has developed from pre-independence where an array of regimes determined inheritance depending on whom they applied to, to an age where a single legislation was made to resolve this multiplicity; the Law of Succession Act. Since then, a new Constitution has been promulgated and the old one repealed. There are certain areas of the Act that resemble the latter more than the former. One such area is that of intestacy. More specifically, the position taken on the one-sided determination of the life interest of a widow upon remarriage. This study tackles this issue and finds that Sections 35(1) and 36(1) are indeed contrary to the entitlement of rights in Article 45(3) guaranteeing equal rights to parties within a marriage. It further advances the argument that this inconsistency has its possible origins in African Customary law and owes its longevity to a foregone constitutional era. The recommendation offered is an amendment to the Act aimed at equalising the parties to a marriage by ensuring parity in the duration of the life interest. In addressing itself on these issues, a synthesis of literature review, case review, legislative review and a key analysis of constitutional preparatory documents is used.